Implementasi Metode Kaizen di Berbagai Industri: Kajian Literatur Sistematis - Manurung, Hasiholan; Sukma, Dias Irawati; Fahturizal, Indra Maulana (Universitas Mercu Buana, 2021)
Increasing productivity and reducing production costs are major factors in improving performance as a way for the advancement of a company or organization. The kaizen method is a proven method and is practiced in variousfieldsin various countries. The purpose of this paper is to identify and explore the implementation of the kaizen method in industry and analyze the benefits obtained. This paper finds a strategy in the form of new regulations that can be updated according to the need to increase productivity and minimize expenditure. The method used is a literature review of various scientific articles related to the implementation of the kaizen method in various industries that have been widely implemented in various fieldsin many countries. The results obtained from the identification of various articlesshow that the kaizen method is very effective in managing the resources owned by a company or organization with a measurable impact and can be adjusted according to circumstances